Thinking Forgetting Through: Maurice Blanchot, for Example (Global Journal of Human-Social Science, 2020)
Much of Blanchot's thought seeks to undo the safe, secure interiority of early Heidegger. It takes the form of a radical nihilism open to the outside, where a swatch of irredeemable negativity exposes language and being to a corrosive contaminant while effacing all transcendental signifieds. The result is the impenitent-the forgetting that antedates all memory. Yet the trace of the immemorial persists and persistently indicates the beyond being, which is the sacred. A light-hearted unconcern-a kind of reduction of ontic appropriativity-then constitutes a way to (of) the outside, a non-place absolutely lacking in an inside. Metaphorically, the insouciance of casual reading (rather than one that digs for the profundity) offers access to an inaccessible text, a text made inaccessible by the reach for meaning. The sacrifice Blanchot has in mind, in going beyond that of the object of thought, requires a total rehabilitation of thinking. Thought as forgetting becomes the dissembled auto-affection of the outside. Such thinking bears the mark of a primordial affirmation, the sacral Yes.